KLASIFIKASI CITRA MULTI WAKTU RESOLUSI TINGGI (GOOGLE EARTH) UNTUK PEMETAAN DINAMIKA PERUBAHAN PENGGUNAAN LAHAN SEPANJANG SUNGAI BATANG ARAU KOTA PADANG - Handi Muhammad Ali Hanafi; Fajrin, Ilham Armi (ADISAM PUBLISHER, 2023)
Land use change or changes in land use are basically the impact of the increasingly rapid population growth in an area as well as the increasing needs of the community for land. by increasing or decreasing other land use classifications from one time to the next, in other words there is a shift in the function of land use as a result of population growth factors such as the case of changing the use of agricultural land to built-up land. This research uses coordinate accuracy testing to determine the differences between the data size field with size data on the edited image. Accuracy checking is carried out using GCP coordinates and distance, it is known that the degree of accuracy depends on the RMS coordinate error or whether or not the RMS distance error value is large, and this research also uses interpretation accuracy testing, the stage of searching for Overall Accuracy calculates the overall percentage of accuracy for the overall interpretation accuracy class is 82 % produce good or decent overall accuracy if using an accuracy reference that is considered appropriate for using satellite imagery of 80% - 85%,.